Building a robot to use in school: teachers and students learning together - Ribeiro, A. Fernando (2008)
Robotics is becoming extremely popular amongst the youngsters, because it is fun, you can practice with hands-on and above all you get real results. Since most students have to develop practical works in their schools, robotics works are becoming very popular. But robotic is a multidisciplinary area of knowledge and therefore the school teachers might not have the know-how in all required fields. The Robotics Group at University of Minho (Guimarães, Portugal), created a new robotics event called RoboParty© where they actually build robots from scratch (mechanics, electronics, programming, etc.) in 3 days (24 hours a day) supervised continuously by experts on the various fields. At the end, they take the robot home with them and they can continue using and improving it later on.